APPLICATION OF SCRAMBLE LEARNING MODEL ON CLASS V AQIDAH AKHLAK SUBJECTS IN MI MIFTAHUL ULUM WIROWONGSO AJUNG JEMBER - Halid, Ahmad; Muhammad Ilyas (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2022)
A model is a description of something that can clarify the various relationships between the elements in the model. In the world of education there are learning models that are used as a reflection in implementing learning in the classroom. A learning model is a guideline in the form of a program or teaching strategy guide designed to achieve a learning goal, and most importantly to create interesting and meaningful learning, such as a scramble learning model. In this research, the focus of the problem is to understand the application of scramble learning model in class V moral beliefs in MI Miftahul Ulum Wirowongso and find out whether the application of scramble learning model in class V moral beliefs can improve learning outcomes in MI Miftahul Ulum Wirowongso. This study uses a descriptive qualitative approach, data collection is done using observation methods, interviews and documentation. While the determination of informants or sources used purposive sampling technique. The collected data were analyzed by data reduction techniques, data presentation and drawing conclusions, while for data validity using data source triangulation. From the results of the analysis, it can be concluded that the application of scramble learning model in the subject of aqidah akhlak class V in its implementation can increase the enthusiasm, activity and discipline and solidarity of learners, can improve the way of thinking quickly and accurately in working on problems. In this application can also improve the learning outcomes of learners